Pentingnya Penggunaan Hutang sebagai Sumber Pembiayaan Modal Kerja dalam Rangka Meningkatkan Profitabilitas pada PT. Mustika Ratu Tbk - Rachmawatik, Arvita Puri; jadi P, Moel (Jurnal Ilmiah Mahasiswa FEB, 2013)
The background of this research is the analysis of the sources and uses of working capital based on the company's financial statements  in the form of balance  that can be  used by  the company's management  in particular  financial managers  to know how a company manages  its working capital  to improve profitability. This study  aims to provide  advice to the  PT. Mustika  Ratu  Tbk  in determining the appropriate financing  to  meet  its working capital  needs  in improving  the company's profitability.  This research  includes  descriptive research  with quantitative methods.  Object  of this study  is  PT.  Mustika  Ratu  Tbk  year observation period  2009-2011.  Data  analysis techniques using  comparative balance sheet  analysis,  analyzing the  sources and uses  of working capital, determine  sales projections,  analyze the  external  funding needs,  determine the indifference  point  between debt  with  common stock,  determine  the  projected EBIT, EBIT-EPS analysis at various  levels of EBIT.The results showed that PT. Mustika  Ratu  need additional capital  amounting to  Rp  53,299,990,284  to be obtained through bank  loans or  issuing new common stock. From the analysis  it can be seen that the expected level of EBIT is greater than his Indifference Point. So the company should use the composition of debt is greater than common stock. With the increasing use of debt, the company will increase EPS when the company earned EBIT EBIT above the indifference point. The company has been trading on the eqity run because  the company used the funds  to  fixed charges  that result in beneficial effects of funds  to holders of ordinary shares are  in form EPS enlarge it. Keywords: Working Capital, Financial  Leverage,  Indifference Point, Earning Before Interest & Tax, and Earning Per Share